Diagnosis and Treatment of Chronic Neuropathic and Mixed Pain in Children and Adolescents: Results of a Survey Study amongst Practitioners - Thomas G. de Leeuw; Tjitske van der Zanden; Simona Ravera; Mariagrazia Felisi; Donato Bonifazi; Dick Tibboel; Adriana Ceci; Florentia Kaguelidou; Saskia N. de Wildt; on behalf of the GAPP Consortium (MDPI AG, 2020)
Validated diagnostic tools to diagnose chronic neuropathic and mixed pain in children are missing. Therapeutic options are often derived from therapeutics for adults. To investigate the international practice amongst practitioners for the diagnosis and treatment of chronic, neuropathic pain in children and adolescents, we performed a survey study among members of learned societies or groups whose members are known to treat pediatric pain. The survey included questions concerning practitioners and practice characteristics, assessment and diagnosis, treatment and medication. We analyzed 117 returned questionnaires, of which 41 (35%) were fully completed and 76 (65%) were partially completed. Most respondents based the diagnosis of neuropathic pain on physical examination (68 (58.1%)), patient history (67 (57.3%)), and underlying disease (59 (50.4%)) combined. Gabapentin, amitriptyline, and pregabalin were the first-choice treatments for moderate neuropathic pain. Tramadol, ibuprofen, amitriptyline, and paracetamol were the first-choice treatments for moderate mixed pain. Consensus on the diagnostic process of neuropathic pain in children and adolescents is lacking. Drug treatment varies widely for moderate, severe neuropathic, and mixed pain. Hence, diagnostic tools and therapy need to be harmonized and validated for use in children.